Special Issue on "Toward Intelligent Internet of Medical Things and its COVID-19 Applications and Beyond" - Hu, Xiping; Ngai, Edith C. H.; Castellano, Ginevra; Hu, Bin; Rodrigues, Joel J. P. C.; Song, Jaeseung (IEEE internet of things journal, 2021)
The Internet of Medical Things (IoMT) is an extension and specialization of that original Internet of Things (IoT) concept, and applies to the interconnectedness of devices, software applications, and data which are specific to the medical industry. IoMT can add smart technologies to medical devices to monitor the progression of a disease away from the doctor's office and learn things that could impact future care guidelines and patients. It can also provide a better way to care for our elderly by tracking vitals and heart performance, glucose and other body systems, and activity and sleeping levels. During the outbreak of pandemic (e.g., COVID-19), IoMT can even be used to detect main symptoms ubiquitously using intelligent sensors and trace the origin of the outbreak based on aggregated IoT data (e.g., geographic mobile data and purchase history). Although most of the contemporary IoMT systems can measure risks, make decisions, and take actions automatically, the lack of emotion-aware abilities will be an obstacle to more harmonious human-machine interaction and more efficient medical process. Besides, mental disorders, such as depression, schizophrenia, and anxiety, have become a more noticeable cause of suffering. The integration of emotion-aware abilities into IoMT can also contribute to monitor emotional dysregulation continuously in subjects with mental disorders or undergoing serious pandemic such as COVID-19, and give these patients personalized therapy recommendations. Research on affective computing has defined a framework to recognize, interpret, and process human affects, but more research is needed to investigate its application to biomedical applications, especially "in the wild" and over extended periods of time, and how to integrate emotion-aware abilities into IoMT organically is still an open question. This special issue aims to create a platform for researchers, developers, and practitioners from both academia and industry to disseminate the state-of-the-art results and to advance the Emotion-Aware ubiquitous computing in IoMT.